Pharmacological properties of thalidomide (α-phthalimido glutarimide), a new sedative hypnotic drug - Somers, G. F. (1960)
Thalidomide (α-phthalimidoglutarimide, “Distaval,” “Contergan”) is a new sedative hypnotic drug which produces no toxic effects when administered orally to animals in massive doses. This lack of toxicity may be due to limited absorption. The drug has a quietening effect on the central nervous system, reducing the voluntary activity of laboratory animals and promoting sleep. Unlike the barbiturate drugs it does not cause an initial excitation in mice, incoordination or narcosis. It potentiates the actions of other central nervous system depressants, in particular the barbiturates. Its sedative effects are counteracted by central nervous system stimulants. It has no deleterious side effects and does not affect the heart, respiration or autonomic nervous system.